Loss of Maternal Annexin A5 Increases the Likelihood of Placental Platelet Thrombosis and Foetal Loss - Ueki, Hiroshi (Nature Publishing Group, 2012)
Antiphospholipid syndrome is associated with an increased risk of thrombosis and pregnancy loss. Annexin A5 (Anxa5) is a candidate autoantigen. It is not known, however, whether endogenous Anxa5 prevents foetal loss during normal pregnancy. We found significant reductions in litter size and foetal weight in Anxa5-null mice (Anxa5-KO). These changes occurred even when only the mother was Anxa5-KO. A small amount of placental fibrin deposition was observed in the decidual tissues, but did not noticeably differ between wild-type and Anxa5-KO mice. However, immunoreactivity for integrin beta 3/CD61, a platelet marker, was demonstrated within thrombi in the arterial canals only in Anxa5-KO mothers. Subcutaneous administration of the anticoagulant heparin to pregnant Anxa5-KO mice significantly reduced pregnancy loss, suggesting that maternal Anxa5 is crucial for maintaining intact placental circulation. Hence, the presence of maternal Anxa5 minimises the risk of thrombosis in the placental circulation and reduces the risk of foetal loss.